Design of a damped vibration absorber to control the resonant vibration of roll. (1st October 2022) - Wang, Ming; Xu, Huidong; He, Dongping; Wang, Tao; Zhang, Jianwen
Abstract: Strip rolling is currently the main steel production process. The vertical vibration of the rolling mill caused by the large reduction ratio and high rolling speed reduces the qualification rate of strip products, and even damages the rolling equipment. In this paper, a new particle damping absorber (PDA) is designed to suppress the vertical vibration of the mill. The adaptive genetic algorithm (AGA) is used to optimize the basic parameters of PDA. Considering the nonlinear stiffness between the roll and the rolling stock, a four-degree-of-freedom vertical vibration model of the roll system with the PDA is established. The amplitude-frequency characteristic equations of the primary resonance and the internal resonance are solved by using the multi-scale method. The static bifurcation of the primary resonance of the system is investigated based on the singularity theory. The effects of parameters on vibration are analyzed. The control effect of the vibration absorber is investigated experimentally, and it is found that the experimental results are basically consistent with the theoretical analysis, which verifies the reliability of the established vibration model. The results show that the PDA can effectively suppress the vertical vibration of the roll. It provides some theoretical guidance for the research on vibration suppression of rolling mills.